Republic of Congo : Interim Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Congo's Interim Poverty Reduction Strategy Paper (I-PRSP). Congo's I-PRSP explains the features and causes of poverty in Congo. It provides a short- and medium-term vision of development as well as a strategic orientation for a return to sustainable and equitable growth. The main objective is steady poverty reduction. The choice and implementation of strategic orientations and priority actions in the I-PRSP are consistent with the government's commitment to rebuilding the economy and in line with the Millennium Development Goals, the New Partnership for Development, and the government's 'nouvelle esperance' program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet